Examining the Impact of Math Anxiety, Scaffolding, and Math Attitude on Working Memory: A Comparative Analysis between Islamic Boarding Schools and Public Schools - Eka Fitria Ningsih; Catharina Asri Budiningsih; Sugiman Sugiman; Tubagus Pamungkas (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
The goal of this research is to investigate models relating to psychological aspects of mathematics learning, such as math anxiety, scaffolding, math attitude, and working memory. This study included 548 junior high school students from public schools and Islamic boarding schools. The analytical method utilizes analysis of variance, bivariate product moment supported by SPSS, and Smart PLS 3 for path analysis. Model fit criteria (SMSR < .05; RMS Theta < .102; NFI > .9). The model fits based on the SRMR value .000 < .10 dan NFI 1 > .90. The findings show that students from public schools and Islamic boarding schools are different in terms of math anxiety, scaffolding and math attitude. Path analysis shows that math attitude mediates the interaction between math anxiety and scaffolding on working memory. Furthermore, scaffolding has a direct impact on working memory. The implications of the study's findings have been discussed in this article.